2009
DOI: 10.1038/nature07637
|View full text |Cite
|
Sign up to set email alerts
|

Intersubunit coordination in a homomeric ring ATPase

Abstract: Homomeric ring-ATPases perform many vital and varied tasks in the cell, ranging from chromosome segregation to protein degradation. Here we report the first direct observation of the inter-subunit coordination and the step size of such a ring-ATPase, the dsDNA packaging motor in the bacteriophage φ29. Using high-resolution optical tweezers, we find that packaging occurs in increments of 10 bp. Statistical analysis of the preceding dwell times reveals that multiple ATPs bind during each dwell, and application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

34
437
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 269 publications
(474 citation statements)
references
References 50 publications
34
437
1
Order By: Relevance
“…In particular, the values of N L and N S indicate that each cycle must contain no less than two ATP binding states and no less than four additional, non-ATP-binding states. Previously, similar conclusions were drawn from the measured value of n min at the highest and lowest concentrations of ATP (5 μM and 1,000 μM ATP), under the assumption that these conditions were sufficiently limiting or saturating for ATP (29). However, limiting or saturating concentrations of [ATP] for the mean dwell time need not be limiting or saturating for n min , and, thus, it was not necessarily obvious that the values of n min measured at the lowest and highest [ATP] were accurate estimates of the asymptotic values of this parameter.…”
Section: Resultsmentioning
confidence: 53%
See 4 more Smart Citations
“…In particular, the values of N L and N S indicate that each cycle must contain no less than two ATP binding states and no less than four additional, non-ATP-binding states. Previously, similar conclusions were drawn from the measured value of n min at the highest and lowest concentrations of ATP (5 μM and 1,000 μM ATP), under the assumption that these conditions were sufficiently limiting or saturating for ATP (29). However, limiting or saturating concentrations of [ATP] for the mean dwell time need not be limiting or saturating for n min , and, thus, it was not necessarily obvious that the values of n min measured at the lowest and highest [ATP] were accurate estimates of the asymptotic values of this parameter.…”
Section: Resultsmentioning
confidence: 53%
“…Additional measurements at high opposing loads revealed that after the dwell, the DNA was packaged not in a single step, but in a burst of four 2.5-bp steps. The observation of four steps per cycle strongly suggests that the motor loads four ATPs to four different subunits during the observed dwells (29). Previous work (29,34) has shown that the mean dwell time is well described by a Michaelis-Menten [ATP] dependence; thus, we expect that the substrate dependence of n min is fit by Eq.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations